Diffusion Behavior of Organic Solvents in Graphene Oxide/Nano Silica Hybrid Natural Rubber Latex Nanocomposite: Experimental and Theoretical Approach - Prajitha Velayudhan; Jibin Keloth Paduvilan; Abitha VK; Sisanth Krishnagehum Sidhardhan; Sabu Thomas (Macromolecular Materials and Engineering)
Abstract This study explores the impact of a graphene oxide (GO)/nano silica (NS) hybrid (GO/NS) filler on the diffusion characteristics of natural rubber (NR) composites when exposed to toluene, xylene, and hexane solvents. The lowest solvent uptake is observed for NR GO/NS 3 (3 phr), which is attributed to forming a robust filler network within the composite. The calculation of crosslink density using the Flory‐Rehner equation reveals significantly higher values for NR GO/NS 3, indicating good crosslinking density in the presence of the hybrid filler. Furthermore, molecular mass between crosslinks (Mc) is calculated, demonstrating a favorable fit with the Affine model. The investigation extends to theoretical modeling, where the Korsemeyer–Peppas and Peppas–Sahlin models are employed to predict solvent uptake behavior. Strikingly, the experimental values exhibit a strong alignment with the Peppas–Sahlin model. This comprehensive analysis provides valuable insights into the diffusion behavior of graphene oxide/nano silica (GO/NS) hybrid‐reinforced natural rubber latex in organic solvents, highlighting potential applications in areas such as solvent‐resistant coatings, barrier materials for chemical storage, and enhanced performance in protective gloves and seals used in harsh chemical environments.